Lethal neonatal rigidity and multifocal seizure syndrome – Report of another family with a BRAT1 mutation. (March 2015) - Straussberg, Rachel; Ganelin-Cohen, Esther; Goldberg-Stern, Hadassah; Tzur, Shay; Behar, Doron M.; Smirin-Yosef, Pola; Salmon-Divon, Mali; Basel-Vanagaite, Lina
Abstract: We describe two siblings born to consanguineous Arab-Muslim parents who presented in early infancy with myoclonic seizures, hypertonia and contractures, arrested head growth, inability to swallow, and bouts of apnea-bradycardia, culminating in cardiac arrest and death. Whole-genome sequencing yielded a c.1173delG mutation in the BRAT1 gene. Three recent reports identified mutations in the same gene in three infants from three Amish sibships, one Mexican neonate and two Japanese siblings with similar clinical manifestations. The authors speculated that the destabilization of the encoded protein may underlie the catastrophic epilepsy and corticobasal neuronal degeneration. We suggest that BRAT1 be added to the growing list of genes that are related to severe early infantile (neonatal) epileptic encephalopathy.